Having a prevention regulatory focus longitudinally predicted distress and health‐protective behaviours during the COVID‐19 pandemic. (12th February 2022) - Rodrigues, David L.; Lopes, Diniz; Balzarini, Rhonda N.
Abstract: People focussed on prevention (vs. promotion) are motivated by safety and are less inclined to take risks. We tested if having a prevention (vs. promotion) focus before the COVID‐19 pandemic outbreak predicted threat perceptions and health outcomes throughout the pandemic. Participants ( N  = 161) took part in a longitudinal study. Measures were assessed before the pandemic was declared (on November 2019, T1) and after a global pandemic was declared (on June 2020, T2). Participants who were more focussed on prevention prior to the onset of the pandemic (at T1) perceived greater risk and were more worried about contracting COVID‐19, and engaged in more preventive behaviours during the pandemic (at T2). They also reported less anxiety and felt healthier later on (at T2). Exploratory analyses revealed that enacting preventive behaviours helped people cope with pandemic‐related anxiety. Being motivated by security and enacting preventive behaviours seems to have helped people reduce anxiety over risk even during the pandemic.